2012
DOI: 10.1134/s1069351312010107
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic variation of local scaling property before Puer M6.4 earthquake in China: The presence of a new pattern of nonlinear behavior of seismicity

Abstract: We observed a new pattern of nonlinear behavior of seismicity. We studied the scaling property of the interevent time series of the seismic sequence for Puer area in China by using the methods of the local scaling property, the generalized dimension spectrum, and the correlation dimension. It is indicated that there are clear characteristic variations of local scaling property and generalized dimension spectrum prior to Puer M6.4 earthquake while there is no characteristic variation of the correlation dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Li and Xu [26,[39][40][41] studied the temporal variation of local scaling property for the series of interevent times between successive earthquakes by using the seismic activity data in several regions of China. We found that there are characteristic changes of local scaling property prior to some large earthquakes.…”
Section: Local Scaling Property Of Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Li and Xu [26,[39][40][41] studied the temporal variation of local scaling property for the series of interevent times between successive earthquakes by using the seismic activity data in several regions of China. We found that there are characteristic changes of local scaling property prior to some large earthquakes.…”
Section: Local Scaling Property Of Seismicitymentioning
confidence: 99%
“…Some methods can only give the description of the monofractal property of seismicity [36], while others can sufficiently give the description of heterogeneous properties of fractal seismic system [37,38]. Besides, the research results of some scale invariance methods (such as the multifractal spectrum, the correlation dimension, the fractal dimension, and Hurst exponent analysis of seismicity) are relatively mature because there have been many studied cases which show characteristic changes of scale invariance of seismicity prior to large earthquakes, while the research results of local scaling property are only tentative [26,[39][40][41] because the observed cases which show characteristic changes of local scaling property of seismicity prior to large earthquakes have been quite few so far.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multidimensional will explain the state from one level to other level of cluster existence, when it saturates at higher value, it indicates that no further cluster exists within cluster. This spatial clustering result can be used to understand the seismicity of a region (Aki, 1981(Aki, , 1984King, 1983;Legrand et al, 1996;Nakaya and Hashimoto, 2002;Oncel and Wilson, 2002, 2004Roy and Ram, 2006;Li and Xu, 2012). This paper presents the application of the correlation integral method for the determination of the correlation dimension and the multifractal or generalized fractal dimension.…”
Section: Introductionmentioning
confidence: 96%
“…These systems are grouped under the umbrella of the chaos theory, and they are useful tools to define the embedded irregularities. The changes in the radon gas level along the fault lines have non-linear behaviours and they are used for the earthquake prediction studies (Cuculeanu and Lupu 1996, Albarello et al 2003, Planiniü et al 2004, Ghosh et al 2007, Das et al 2009, KülahcÕ et al 2009, Qiang and Gui-Ming 2012.…”
Section: Introductionmentioning
confidence: 99%